Providing Interprofessional Learning Experiences for Students of Health and Social Care: The SOYAÇ Model from Istanbul. - GÜR, Kamer; KOLAÇ, Nurcan; KURT, Seher; ÇALIK, Burcu TÜMERDEM; BEYHAN, Abdullah; BADEMCİ, Özden (Fenerbahce University Journal of Health Sciences (FBU-JOSH) / Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2024)
The aim of our research was to determine the effectiveness of a six-month, community-based intervention on student interns’ perceptions of interdisciplinary education and interprofessional learning. All participants were registered volunteers attending the We’re at School in Üsküdar internship program coordinated by the Maltepe University Research and Application Center for Children Living and Working on the Street (Turkish acronym SOYAÇ). This model offers students of health and social care an immersive 5 days a week experience over a duration of 6 months, providing cooperative, multidisciplinary applications in a community-based context in Istanbul. A quasi-experimental, pre-post approach was used. The sample consists of 43 undergraduate and graduate students studying in the Health and Social Care Departments of two SOYAÇ stakeholder universities. Data collection tools are the Interdisciplinary Education Perception Scale and Interprofessional Learning Scale. We found increases and significant differences in posttest scores for Interprofessional Learning, Competence and Autonomy, Perception of Actual Cooperation, Readiness for Learning, and Professional Identity (p<0.05). Our findings confirm a significant beneficial impact of the SOYAÇ Model on student perceptions of interacting and cooperating with other vocations.